Abandonment practices through the microscope lens. Microarchaeological data from Middle Bronze Age Erimi, Cyprus. (1st September 2020) - Amadio, Marialucia; Boaretto, Elisabetta; Bombardieri, Luca
Abstract : Abandonment sequences at Middle Bronze Age Erimi have been examined using integrated stratigraphic analysis and high-resolution microarchaeological techniques, with the aim of investigating the environmental processes and socio-cultural practices that impacted on the abandonment of buildings and settlement areas. The data revealed the occurrence of two distinct processes: gradual structural degradation and rapid destruction by a fire event. Destruction sequences within burnt buildings were examined to identify the temperatures to which sediments had been exposed and to reconstruct the conflagration event. Resulting data are discussed in the context of Middle Bronze Age Cyprus, in a preliminary consideration of the ideological implications of the identified abandonment practices.